Concentrations of synovial fluid biomarkers and the prediction of knee osteoarthritis 16 years after anterior cruciate ligament injury. Issue 4 (April 2017) - Neuman, P.; Dahlberg, L.E.; Englund, M.; Struglics, A.
Summary: Objective: To describe the longitudinal patterns of release, and investigate the association between a set of synovial fluid biomarkers at the acute and chronic stage and the development of radiographic knee osteoarthritis (OA) after an anterior cruciate ligament (ACL) injury. Design: Synovial fluid was aspirated from the acutely ACL-injured knee within the first 2weeks (acute samples), and yearly (chronic samples) up to 7.5 years after injury in 88 subjects (60% men). Non-injured subjects ( n  = 12) were used as reference group. Aggrecan, cartilage oligomeric matrix protein (COMP), matrix metalloproteinase (MMP)-3 and tissue inhibitor of metalloproteinase (TIMP)-1 in synovial fluid were quantified by immunoassays. The presence of radiographic tibiofemoral (TF) or patellofemoral (PF) OA [Kellgren and Lawrence (K&L) ≥2] was examined with weight-bearing knee radiography 16 years after the ACL injury. Results: The average acute and chronic SF concentrations of COMP and aggrecan were elevated in comparison with the reference group ( P  < 0.001). The levels of COMP and aggrecan clearly decreased approximately half a year after the ACL injury, and returned to reference values during the 7.5 years of follow-up. Using logistic regression analysis neither acute nor chronic concentrations of the four biomarkers were associated with the development of radiographic knee OA at the 16 year follow-up. Conclusion: Increased synovial fluid concentrations of aggrecan and COMP was related to knee injury, but acute and chronic synovial fluid concentrations of aggrecan, COMP, MMP-3 and TIMP-1 failed to predict knee OA 16 years after ACL injury.